Porous adsorption material for purifying organic waste gas and preparation method of porous adsorption material
By loading tungsten trioxide and UiO-66 on the titanium carbide MXene support, porous adsorption materials are formed, which solves the problems of degradation of catalyst activity and insufficient performance of traditional photocatalytic materials, and achieves efficient VOCs removal and long-term stable operation.
Patent Information
- Application Number
- CN202510052610.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-01-14
AI Technical Summary
When the prior art treats VOCs of complex components, the activity of the catalyst is prone to decrease or inactivated, and traditional photocatalytic materials have defects such as narrow light response range and weak adsorption capacity, making it difficult to operate stably in complex environments for a long time.
By using titanium carbide MXene as a support, loading tungsten trioxide and UiO-66 metal organic frames, a porous adsorption material is formed. This material enhances the adsorption and catalytic degradation of VOCs by optimizing structural design, improving the specific surface area and pore size distribution, and combining precious metal nanoparticles or modified semiconductor materials.
It significantly improves the removal efficiency of VOCs, extends the service life of the photocatalyst, enhances the anti-toxicity ability, and improves the photocatalytic efficiency.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous adsorption materials, in particular to a porous adsorption material for purifying organic waste gas and a preparation method thereof. Background Art
[0002] Volatile Organic Compounds (VOCs), as the main precursors of ozone and fine particulate matter PM2.5, are one of the important causes of complex air pollution in my country. Excessive release of VOCs not only seriously threatens the ecological environment, but also poses a huge threat to human health. Therefore, how to efficiently control VOCs has become an environmental problem that needs to be solved urgently.
[0003] At present, there are various technical means to control VOCs. Among them, catalytic oxidation technology is considered to be one of the most effective methods for VOCs removal due to its mature process, simple operation, high efficiency, low energy, and no secondary pollution. The key to catalytic oxidation technology is to find an efficient and stable catalyst. Supported precious metal catalysts are usually used for the efficient degradation of VOCs because of their high catalytic activity under low temperature conditions. However, since the VOCs emitted under actual working conditions contain a variety of complex components, these components often have a poisonous effect on the active components of the catalyst, resulting in a decrease in the activity of the catalyst or even inactivation.
[0004] In recent years, Metal-Organic Frameworks (MOFs) materials have received extensive attention in response to the problem of catalyst deactivation in complex environments. MOFs have high specific surface area, adjustable pore structure and excellent chemical stability. In particular, zirconium (Zr)-based UiO-66 has become an ideal carrier for supported precious metal catalysts due to its high hydrothermal stability and excellent loading capacity for precious metals. By loading precious metal nanoparticles on Zr-based UiO-66, not only can the dispersion and stability of precious metals be effectively improved, but also the structural characteristics of UiO-66 can enhance the catalyst's adsorption capacity for VOCs, thereby improving the catalytic efficiency.
[0005] In addition to catalytic oxidation technology, photocatalytic technology has also been widely studied in the removal of VOCs due to its advantages such as simple equipment, easy operation and sustainability. Photocatalytic technology based on traditional semiconductor materials can effectively degrade VOCs under ultraviolet or visible light irradiation without generating secondary pollution. However, traditional semiconductor photocatalysts have some inherent defects, such as high recombination rate of photogenerated carriers, narrow light response range, weak adsorption capacity for VOCs, and easy accumulation of degradation intermediates to deactivate them. These defects limit the performance and efficiency of traditional photocatalytic materials in practical applications.
[0006] Based on the above background, the development of a porous material with both efficient catalytic and adsorption properties that can operate stably for a long time in complex environments has become a hot topic in current research. MOFs materials represented by Zr-based UiO-66 have shown great application potential in the field of supported precious metal catalysts and photocatalysts due to their unique physical and chemical properties. By optimizing the structural design of MOFs, further improving their specific surface area, pore size distribution and chemical stability, and combining them with precious metal nanoparticles or modified semiconductor materials, it is expected to significantly improve the removal efficiency of VOCs and provide a new and efficient solution for the purification of organic waste gas.
[0007] Therefore, the present invention aims to provide a porous adsorption material based on MOFs materials, especially Zr-based UiO-66 and its preparation method, so as to achieve efficient adsorption and catalytic degradation of complex component VOCs, overcome the deficiencies in the prior art, and promote the development of VOCs treatment technology in a more efficient and stable direction. This new material is not only suitable for VOCs treatment in the wood industry, but also can be widely used in organic waste gas purification in other industries, making important contributions to air pollution control and environmental protection. Summary of the invention
[0008] The object of the present invention is to provide a porous adsorption material for purifying organic waste gas and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a porous adsorption material for purifying organic waste gas comprises the following steps: S1: Add lithium fluoride to hydrochloric acid solution, stir evenly, add carbon aluminum titanium MXene, heat to 35-38 ° C and stir for 24 hours, add the mixed solution to deionized water, centrifuge and wash until pH is neutral, filter, ultrasonically disperse the precipitate in deionized water, centrifuge, take the supernatant, and obtain thin flake titanium carbide MXene; Furthermore, the mass ratio of lithium fluoride to carbon aluminum titanium MXene is 1:1; Furthermore, the concentration of the hydrochloric acid solution is 27-28wt%, S2: Add sodium tungstate dihydrate to deionized water, add 0.3M hydrochloric acid to adjust the pH to 1.2-1.3, add oxalic acid solution and ammonium sulfate in sequence, stir evenly, add thin flake titanium carbide MXene, ultrasonically disperse, heat to 180-185°C for reaction for 16-18h, filter, wash with deionized water and ethanol, vacuum dry at 80°C, heat to 450°C for calcination for 1-2h, and obtain modified titanium carbide MXeneA; Furthermore, the mass ratio of sodium tungstate dihydrate: oxalic acid: ammonium sulfate: thin-sheet titanium carbide MXene is (9.277-9.7408): (7.0900-7.4445): (28.1250-29.5312): 5.01; Further, the concentration of the oxalic acid solution is 105.037 mM; S3: Add zirconium chloride and terephthalic acid to N,N-dimethylformamide, dissolve by ultrasonication, add modified titanium carbide MXeneA, heat to 120°C for crystallization for 24h, cool to room temperature, filter, wash with N,N-dimethylformamide and ethanol, and dry under vacuum at 70-80°C to obtain modified titanium carbide MXeneB; Furthermore, the mass ratio of zirconium chloride: terephthalic acid: modified titanium carbide MXeneA is (0.28-0.53): (0.19-0.34): 5.01; S4: Add the modified titanium carbide MXeneB to the zinc nitrate aqueous solution, heat to 60-65°C for reaction for 1-1.5h, add sodium carbonate solution to adjust the pH to 7-7.5, keep warm for reaction for 5-5.5h, let stand and cool for 1h, filter, wash the filtrate with deionized water until the pH is neutral, dry in vacuum at 110°C, and calcine at 250-300°C for 3.5-4h to obtain the modified titanium carbide MXeneC; Furthermore, the mass ratio of the modified titanium carbide MXeneB: zinc nitrate aqueous solution is (0.618-0.976):(0.86-1.3588); Further, the concentration of the zinc nitrate aqueous solution is 0.5M, and the concentration of the sodium carbonate solution is 0.5M; S5: Ultrasonic disperse the modified titanium carbide MXeneC in ethylene glycol, add palladium acetate solution, stir evenly, heat to 150-155°C for reaction for 2-2.5h, cool to room temperature, filter, wash with deionized water and ethanol, and vacuum dry at 70°C for 12h to obtain a porous adsorption material.
[0010] Further, the concentration of the modified titanium carbide MXeneC: palladium acetate solution is 1:(1-2); Furthermore, the concentration of the palladium acetate solution is 0.03M.
[0011] Compared with the prior art, the beneficial effects achieved by the present invention are: The present invention uses titanium carbide MXene with large specific surface and high surface activity as a carrier, first loads a large amount of needle-rod tungsten trioxide (modified titanium carbide MXeneA) on its surface, uses tungsten trioxide as a secondary carrier, and synthesizes UiO-66 metal organic framework (modified titanium carbide MXeneB) on its surface, which maximizes the loading amount of UiO-66 per unit area. At the same time, due to the needle-rod structure of tungsten trioxide, the contact area between UiO-66 and VOCs pollutants can be greatly increased, which can not only expand the light response range of the photocatalyst, but also utilize the porous structure and high specific surface area of MOFs to enhance the adsorption capacity of VOCs, thereby reducing the recombination rate of photogenerated carriers and improving the photocatalytic efficiency. In addition, the adjustable pore size and excellent chemical stability of MOFs materials make them show stronger anti-toxicity in the process of photocatalytic degradation, effectively extending the service life of the photocatalyst.
[0012] The present invention controls the calcination temperature during the preparation of tungsten trioxide-loaded titanium carbide MXene, so that a large number of titanium dioxide nanoparticles grow evenly on the edge of the titanium carbide MXene, which alleviates the stacking of titanium carbide MXene sheets, is beneficial to the improvement of the overall specific surface area of the composite material and the increase of adsorption sites, and further improves the photocatalytic performance of the porous adsorption material.
[0013] The present invention further uses UiO-66 as a carrier, which is different from the traditional single-loaded catalyst Pd. Zinc oxide is encapsulated inside UiO-66 (modified titanium carbide MXeneC) and catalyst Pd nanoparticles are loaded on the surface of UiO-66 (porous adsorption material) in the form of inner encapsulation and outer loading. The purpose is to maximize the use of space to load multiple catalysts per unit volume, and to control the reaction variables to avoid blocking the pores by encapsulated zinc oxide and surface-loaded Pd nanoparticles, so as to achieve the purpose of purifying VOCs organic waste gas through adsorption catalytic oxidation technology. DETAILED DESCRIPTION
[0014] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0015] In the following examples, the carbon aluminum titanium MXene has a specification of 400 mesh and is purchased from Eleven Technology Co., Ltd.; the remaining raw materials are commercially available.
[0016] Example 1: A method for preparing a porous adsorption material for organic waste gas purification: S1: Add 30 mL of 37% v / v hydrochloric acid to 10 mL of deionized water, add 2 g of lithium fluoride, stir evenly, add 2 g of carbon aluminum titanium MXene, heat to 35 ° C and stir for 24 hours, add the mixed solution to deionized water, centrifuge at 3500 r to wash until pH is neutral, add deionized water and filter to collect the precipitate, ultrasonically disperse the precipitate in deionized water at 900 W, centrifuge at 3500 r, take the supernatant, and obtain a thin flake titanium carbide MXene; S2: 7.4445 g of oxalic acid was diluted to 750 mL to obtain an oxalic acid solution, 9.7408 g of sodium tungstate dihydrate was added to 300 mL of deionized water, 0.3 M hydrochloric acid was added to adjust the pH to 1.2, oxalic acid solution and 29.5312 g of ammonium sulfate were added in sequence, and the mixture was stirred evenly, 5.01 g of thin titanium carbide MXene was added, ultrasonic dispersion was performed, the mixture was heated to 180 ° C for 16 h, the mixture was filtered, the mixture was washed with deionized water and ethanol, vacuum dried at 80 ° C, and the mixture was heated to 450 ° C for calcination for 1 h to obtain modified titanium carbide MXene A; S3: Add 0.28g zirconium chloride and 0.19g terephthalic acid to 50mL N,N-dimethylformamide, dissolve by ultrasonication, add 5.01g modified titanium carbide MXeneA, heat to 120°C for crystallization for 24h, cool to room temperature, filter, wash with N,N-dimethylformamide and ethanol, and dry in vacuum at 70°C to obtain modified titanium carbide MXeneB; S4: 0.618 g of modified titanium carbide MXene B was added to 0.86 g of zinc nitrate aqueous solution, heated to 60 ° C for 1 h, sodium carbonate solution was added to adjust the pH to 7, the reaction was kept warm for 5 h, and the mixture was allowed to stand and cool for 1 h. The mixture was filtered, and the filtrate was washed with deionized water until the pH was neutral. The mixture was vacuum dried at 110 ° C, and calcined at 250 ° C for 4 h to obtain modified titanium carbide MXene C. S5: Ultrasonic disperse 1 g of modified titanium carbide MXeneC in ethylene glycol, add 1 g of palladium acetate solution, stir evenly, heat to 150 ° C to react for 2 h, cool to room temperature, filter, wash with deionized water and ethanol, and vacuum dry at 70 ° C for 12 h to obtain a porous adsorption material.
[0017] Example 2: A method for preparing a porous adsorption material for organic waste gas purification: S1: Add 30 mL of 37% v / v hydrochloric acid to 10 mL of deionized water, add 2 g of lithium fluoride, stir evenly, add 2 g of carbon aluminum titanium MXene, heat to 35 ° C and stir for 24 hours, add the mixed solution to deionized water, centrifuge at 3500 r to wash until pH is neutral, add deionized water and filter to collect the precipitate, ultrasonically disperse the precipitate in deionized water at 900 W, centrifuge at 3500 r, take the supernatant, and obtain a thin flake titanium carbide MXene; S2: 7.4445 g of oxalic acid was diluted to 750 mL to obtain an oxalic acid solution, 9.7408 g of sodium tungstate dihydrate was added to 300 mL of deionized water, 0.3 M hydrochloric acid was added to adjust the pH to 1.2, oxalic acid solution and 29.5312 g of ammonium sulfate were added in sequence, and the mixture was stirred evenly, 5.01 g of thin titanium carbide MXene was added, ultrasonic dispersion was performed, the mixture was heated to 180 ° C for 16 h, the mixture was filtered, the mixture was washed with deionized water and ethanol, vacuum dried at 80 ° C, and the mixture was heated to 450 ° C for calcination for 1 h to obtain modified titanium carbide MXene A; S3: Add 0.53 g zirconium chloride and 0.34 g terephthalic acid to 50 mL N, N-dimethylformamide, dissolve by ultrasonication, add 5.01 g modified titanium carbide MXeneA, heat to 120 ° C for crystallization for 24 h, cool to room temperature, filter, wash with N, N-dimethylformamide and ethanol, and dry in vacuo at 70 ° C to obtain modified titanium carbide MXeneB; S4: 0.618 g of modified titanium carbide MXene B was added to 0.86 g of zinc nitrate aqueous solution, heated to 60 ° C for 1 h, sodium carbonate solution was added to adjust the pH to 7, the reaction was kept warm for 5 h, and the mixture was allowed to stand and cool for 1 h. The mixture was filtered, and the filtrate was washed with deionized water until the pH was neutral. The mixture was vacuum dried at 110 ° C, and calcined at 250 ° C for 4 h to obtain modified titanium carbide MXene C. S5: Ultrasonic disperse 1 g of modified titanium carbide MXeneC in ethylene glycol, add 1 g of palladium acetate solution, stir evenly, heat to 150 ° C to react for 2 h, cool to room temperature, filter, wash with deionized water and ethanol, and vacuum dry at 70 ° C for 12 h to obtain a porous adsorption material.
[0018] Example 3: A method for preparing a porous adsorption material for organic waste gas purification: S1: Add 30 mL of 37% v / v hydrochloric acid to 10 mL of deionized water, add 2 g of lithium fluoride, stir evenly, add 2 g of carbon aluminum titanium MXene, heat to 35 ° C and stir for 24 hours, add the mixed solution to deionized water, centrifuge at 3500 r to wash until pH is neutral, add deionized water and filter to collect the precipitate, ultrasonically disperse the precipitate in deionized water at 900 W, centrifuge at 3500 r, take the supernatant, and obtain a thin flake titanium carbide MXene; S2: 7.4445 g of oxalic acid was diluted to 750 mL to obtain an oxalic acid solution, 9.7408 g of sodium tungstate dihydrate was added to 300 mL of deionized water, 0.3 M hydrochloric acid was added to adjust the pH to 1.2, oxalic acid solution and 29.5312 g of ammonium sulfate were added in sequence, and the mixture was stirred evenly, 5.01 g of thin titanium carbide MXene was added, ultrasonic dispersion was performed, the mixture was heated to 180 ° C for 16 h, the mixture was filtered, the mixture was washed with deionized water and ethanol, vacuum dried at 80 ° C, and the mixture was heated to 450 ° C for calcination for 1 h to obtain modified titanium carbide MXene A; S3: Add 0.28g zirconium chloride and 0.19g terephthalic acid to 50mL N,N-dimethylformamide, dissolve by ultrasonication, add 5.01g modified titanium carbide MXeneA, heat to 120°C for crystallization for 24h, cool to room temperature, filter, wash with N,N-dimethylformamide and ethanol, and dry in vacuum at 70°C to obtain modified titanium carbide MXeneB; S4: 0.618 g of modified titanium carbide MXene B was added to 0.86 g of zinc nitrate aqueous solution, heated to 60 ° C for 1 h, sodium carbonate solution was added to adjust the pH to 7, the reaction was kept warm for 5 h, and the mixture was allowed to stand and cool for 1 h. The mixture was filtered, and the filtrate was washed with deionized water until the pH was neutral. The mixture was vacuum dried at 110 ° C, and calcined at 250 ° C for 4 h to obtain modified titanium carbide MXene C. S5: Ultrasonic disperse 1 g of modified titanium carbide MXeneC in ethylene glycol, add 2 g of palladium acetate solution, stir evenly, heat to 150 ° C to react for 2 h, cool to room temperature, filter, wash with deionized water and ethanol, and vacuum dry at 70 ° C for 12 h to obtain a porous adsorption material.
[0019] Comparative Example 1: A method for preparing a porous adsorption material for organic waste gas purification: S2: 7.4445 g of oxalic acid was diluted to 750 mL to obtain an oxalic acid solution, 9.7408 g of sodium tungstate dihydrate was added to 300 mL of deionized water, 0.3 M hydrochloric acid was added to adjust the pH to 1.2, oxalic acid solution and 29.5312 g of ammonium sulfate were added in sequence, and stirred evenly, 5.01 g of thin titanium carbide MXene was added, ultrasonically dispersed, heated to 180 ° C for 16 h, filtered, washed with deionized water and ethanol, vacuum dried at 80 ° C, heated to 350 ° C for calcination for 1 h, and modified titanium carbide MXeneA was obtained; The remaining steps are the same as those in Example 1.
[0020] Comparative Example 2: A method for preparing a porous adsorption material for organic waste gas purification: S2: 7.4445 g of oxalic acid was diluted to 750 mL to obtain an oxalic acid solution, 9.7408 g of sodium tungstate dihydrate was added to 300 mL of deionized water, 0.3 M hydrochloric acid was added to adjust the pH to 1.2, oxalic acid solution and 29.5312 g of ammonium sulfate were added in sequence, and stirred evenly, 5.01 g of thin titanium carbide MXene was added, ultrasonically dispersed, heated to 180 ° C for 16 h, filtered, washed with deionized water and ethanol, vacuum dried at 80 ° C, heated to 550 ° C for calcination for 1 h, and modified titanium carbide MXeneA was obtained; The remaining steps are the same as those in Example 1.
[0021] Comparative Example 3: A method for preparing a porous adsorption material for organic waste gas purification: S3: 0.57 g zirconium chloride and 0.36 g terephthalic acid were added to 50 mL N, N-dimethylformamide, ultrasonically dissolved, 5.01 g modified titanium carbide MXeneA was added, heated to 120 ° C for crystallization for 24 h, cooled to room temperature, filtered, washed with N, N-dimethylformamide and ethanol, and vacuum dried at 70 ° C to obtain modified titanium carbide MXene B; The remaining steps are the same as those in Example 1.
[0022] Comparative Example 4: A method for preparing a porous adsorption material for organic waste gas purification: S4: 0.618 g of modified titanium carbide MXene B was added to 1.4 g of zinc nitrate aqueous solution, heated to 60° C. for reaction for 1 h, sodium carbonate solution was added to adjust the pH to 7, the reaction was kept warm for 5 h, cooled for 1 h, filtered, the filtrate was washed with deionized water until the pH was neutral, vacuum dried at 110° C., and calcined at 250° C. for 4 h to obtain modified titanium carbide MXene C; The remaining steps are the same as those in Example 1.
[0023] Comparative Example 5: A method for preparing a porous adsorption material for organic waste gas purification: S3: 0.23 g zirconium chloride and 0.19 g amino-terephthalic acid were added to 50 mL N, N-dimethylformamide, ultrasonically dissolved, 5.01 g modified titanium carbide MXeneA was added, heated to 120 ° C for crystallization for 24 h, cooled to room temperature, filtered, washed with N, N-dimethylformamide and ethanol, and vacuum dried at 70 ° C to obtain modified titanium carbide MXeneB; The remaining steps are the same as those in Example 1.
[0024] Comparative Example 6: A method for preparing a porous adsorption material for organic waste gas purification: S5: Add 1g of modified titanium carbide MXeneC to 1g of palladium acetate solution, stir evenly, dry at room temperature overnight, vacuum dry at 70°C for 12h, heat to 200°C under a hydrogen atmosphere and reduce for 2h to obtain a porous adsorption material.
[0025] The remaining steps are the same as those in Example 1.
[0026] Experiment: The porous adsorption material is pressed into tablets by a powder tablet press and then the particles with a size of 20-60 mesh are screened out.
[0027] VOCs catalytic degradation performance test: The porous adsorbent material was placed in a U-shaped quartz reaction tube. Toluene liquid was introduced into the vaporization chamber for vaporization by a 30% O2 / Ar mixed gas with a flow rate of 35 mL / min and a high-purity Ar with a flow rate of 15 mL / min at a certain injection rate through an injector and a syringe pump. The concentration of toluene was controlled to be 1000 ppm by adjusting the injection rate. The total gas flow rate of the reaction was 50 mL / min, and the space velocity was 30000 mL / (g·h); the initial concentration of toluene, the concentration of toluene after the reaction, and the concentration of CO2 were detected by an online gas chromatograph equipped with two hydrogen flame ionization detectors.
[0028] VOCs t =1-C t / C0×100%; Among them, VOCs t is the VOCs conversion rate; C t is the concentration of VOCs after the reaction (ppm); C0 is the initial concentration of VOCs (ppm).
[0029] The temperature at which the VOCs conversion rate reached 90% was recorded to evaluate the catalytic degradation performance.
[0030] Porous adsorption material water resistance performance test: Before 35 mL / min of 30% O2 / Ar and 15 mL / min of Ar enter the vaporization chamber, pass deionized water into the bubbler. Water vapor is introduced into the reaction system by gas carrying. The bubbler is placed in a water bath, and the saturated vapor pressure of water vapor is changed by adjusting the temperature of the water bath, thereby controlling the content of water vapor introduced into the reaction system. Other conditions remain unchanged.
[0031] W=φP v / P; Where W is the water vapor content (vol.%); φ is the relative humidity (%); P v is the saturated vapor pressure of water vapor at a specific temperature (Pa); P is the standard atmospheric pressure (Pa).
[0032] The VOCs conversion rate was measured when the reaction system contained 20.0 vol.% water vapor, and the temperature when the VOCs conversion rate reached 90% was recorded to evaluate the catalytic degradation performance.
[0033] Photocatalytic performance test: A light source was set 15 cm above the quartz reaction tube, and the porous adsorption material was placed in the quartz reaction tube. The 37% v / v formaldehyde solution was heated to 90°C, and the formaldehyde gas was evaporated into the reaction tube. The humidity in the reaction tube was adjusted by bubbling to simulate the real environmental conditions. It was placed in the dark for 60 minutes to reach the adsorption-desorption equilibrium, and then the light was turned on. After a fixed light exposure time, an air pump combined with a gas flow meter was used to take samples. Finally, based on the color reaction between formaldehyde and acetylacetone, the formaldehyde concentration and formaldehyde degradation rate were calculated according to the method in the international standard ISO4614 and the national standard GB / T15516-1195 "Determination of formaldehyde in air quality - acetylacetone spectrophotometry".
[0034] PA t =1-P t / P0×100%; Among them, PA t is the formaldehyde conversion rate; P t / is the concentration of formaldehyde after the reaction (ppm); P0 is the initial concentration of formaldehyde (ppm).
[0035] The experimental data are shown in Table 1 below.
[0036] Table 1 Porous adsorption material performance test data
[0037] Conclusion: The porous adsorption material prepared by the present invention has excellent organic waste gas purification function.
[0038] In Comparative Example 1, the calcination temperature is too low, and fewer irregular titanium dioxide nanoparticles grow on the edge of the titanium carbide MXene, which reduces the catalytic performance. At the same time, it is not conducive to the dispersion of titanium carbide MXene flakes (the flakes are easy to stack), as well as the increase in specific surface area and adsorption sites, resulting in reduced performance.
[0039] In Comparative Example 2, the calcination temperature is too high, resulting in dense titanium dioxide particles grown from the titanium carbide MXene completely encapsulating the titanium carbide MXene, destroying the lamellar structure and causing performance degradation.
[0040] In comparative example 3, the amount of UiO-66 loaded on the surface of titanium carbide MXene by rod-shaped tungsten trioxide is too much, resulting in a large amount of deposition that blocks the photocatalytic effect, is not conducive to the photocatalytic reaction, and leads to reduced performance.
[0041] In comparative example 4, too much metal is filled inside UiO-66, resulting in a significant reduction in pore volume, pore blockage, distortion or loss of connecting ligands, and destruction of the orderliness of the MOF structure, leading to reduced performance.
[0042] Comparative Example 5: Pd loading on the surface of UiO-66 0The number of species is reduced, resulting in reduced performance.
[0043] In comparative example 6, NH2 functionalized UiO-66. The introduction of NH2 into UiO-66 resulted in a decrease in the spatial volume and an increase in the weight of MOFs. After loading Pd, the specific surface area and total controlled volume of MOFs decreased, resulting in reduced performance.
[0044] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a porous adsorption material for purification of organic waste gas, characterized in that: The following steps are involved: The modified titanium carbide MXeneC was ultrasonically dispersed in ethylene glycol, palladium acetate solution was added, stirred evenly, heated for reaction, cooled to room temperature, filtered, washed with deionized water and ethanol, and vacuum dried at 70°C for 12 hours to obtain a porous adsorption material.
2. The method for preparing a porous adsorption material for purifying organic waste gas according to claim 1, characterized in that: The mass ratio of the modified titanium carbide MXeneC to the palladium acetate solution is 1:(1-2); the heating reaction temperature is 150-155° C., and the heating reaction time is 2-2.5 h.
3. The method for preparing a porous adsorption material for purifying organic waste gas according to claim 1, characterized in that: The preparation method of the modified titanium carbide MXeneC comprises the following steps: The modified titanium carbide MXeneB was added to the zinc nitrate aqueous solution, heated to 60-65°C for reaction for 1-1.5h, sodium carbonate solution was added to adjust the pH to 7-7.5, the reaction was kept warm for 5-5.5h, the mixture was allowed to stand and cool for 1h, filtered, the filtrate was washed with deionized water until the pH was neutral, vacuum dried at 110°C, and calcined to obtain the modified titanium carbide MXeneC.
4. The method for preparing a porous adsorption material for purifying organic waste gas according to claim 3, characterized in that: The mass ratio of the modified titanium carbide MXene B: zinc nitrate aqueous solution is (0.618-0.976):(0.86-1.3588); the calcination temperature is 250-300° C., and the calcination time is 3.5-4 h.
5. The method for preparing a porous adsorption material for purifying organic waste gas according to claim 3, characterized in that: The preparation method of the modified titanium carbide MXeneB comprises the following steps: Zirconium chloride and terephthalic acid are added to N,N-dimethylformamide, ultrasonically dissolved, modified titanium carbide MXeneA is added, heated to 120°C for crystallization for 24 hours, cooled to room temperature, filtered, washed with N,N-dimethylformamide and ethanol, and vacuum dried at 70-80°C to obtain modified titanium carbide MXeneB.
6. The method for preparing a porous adsorption material for purifying organic waste gas according to claim 5, characterized in that: The mass ratio of zirconium chloride: terephthalic acid: modified titanium carbide MXeneA is (0.28-0.53): (0.19-0.34): 5.
01.
7. The method for preparing a porous adsorption material for purifying organic waste gas according to claim 5, characterized in that: The preparation method of modified titanium carbide MXeneA comprises the following steps: Sodium tungstate dihydrate is added to deionized water, 0.3M hydrochloric acid is added to adjust the pH to 1.2-1.3, oxalic acid solution and ammonium sulfate are added in sequence, stirred evenly, thin flake titanium carbide MXene is added, ultrasonic dispersion is performed, the reaction is heated to 180-185°C for 16-18h, filtered, washed with deionized water and ethanol, dried in vacuo at 80°C, and calcined to obtain modified titanium carbide MXeneA.
8. The method for preparing a porous adsorption material for purifying organic waste gas according to claim 7, characterized in that: The mass ratio of sodium tungstate dihydrate: oxalic acid: ammonium sulfate: thin-sheet titanium carbide MXene is (9.277-9.7408):(7.0900-7.4445):(28.1250-29.5312):5.01; the calcination temperature is 450°C, and the calcination time is 1-2h.
9. The method for preparing a porous adsorption material for purifying organic waste gas according to claim 7, characterized in that: The method for preparing the thin titanium carbide MXene comprises the following steps: Add lithium fluoride to the hydrochloric acid solution, stir evenly, add carbon aluminum titanium MXene, heat to 35-38 ° C and stir for 24 hours, add the mixed solution to deionized water, centrifuge and wash until the pH is neutral, filter, ultrasonically disperse the precipitate in deionized water, centrifuge, and take the supernatant to obtain thin flake titanium carbide MXene; The mass ratio of lithium fluoride to carbon aluminum titanium MXene is 1:
1.
10. The porous adsorption material prepared according to the method for preparing a porous adsorption material for purifying organic waste gas according to any one of claims 1 to 9.
Citation Information
Patent Citations
Mercapto-aryl functionalized MXene material and preparation method and application thereof
CN111302992A
Method for preparing supported ruthenium metal cluster catalyst through coordination regulation and application
CN114059095A
Cited By
Preparation method of transition metal doped hierarchical porous carbon applied to co-adsorption of multiple VOCs (Volatile Organic Compounds)
CN120679485A
A preparation method of metal-doped multi-level porous carbon applied to co-adsorption of various VOCs
CN120679485B
Adsorbent for recovering precious metals in refining wastewater and preparation method thereof
CN121797265A